2012
DOI: 10.1162/jocn_a_00213
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Affective Priming in Music and Speech

Abstract: The phenomenon of affective priming has caught scientific interest for over 30 years, yet the nature of the affective priming effect remains elusive. This study investigated the underlying mechanism of cross-modal affective priming and the influence of affective incongruence in music and speech on negativities in the N400 time-window. In Experiment 1, participants judged the valence of affective targets (affective categorization). We found that music and speech targets were evaluated faster when preceded by af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 61 publications
4
51
1
2
Order By: Relevance
“…The latency of this effect in our study may well reflect an N400-like effect, which is in general agreement with several previous studies showing N400-like enhanced negativity for semantically incongruous AV signals (e.g. Meyer, Harrison, & Wuerger, 2013;Proctor & Meyer, 2011;Zimmer et al, 2010) and affectively incongruous AV stimuli (Goerlich et al, 2012). While the N400 is generally associated with incongruences in linguistic stimuli (for a review, see Kutas & Federmeier, 2011), the N400 has also been shown to be evoked by nonlinguistic incongruency related to, for example, line drawing and sounds (Cummings, Moreover, the linguistic N400 component is usually reported as a centro-parieto deflection (Kutas & Federmeier, 2011), whereas the current data indicates a more frontal effect, in line with the topography from studies on the non-linguistic N400 (Cummings, Čeponienė, Koyama, Saygin, Townsend, & Dick, 2006;Ganis, Kutas, & Sereno, 1996).…”
Section: Discussionsupporting
confidence: 93%
“…The latency of this effect in our study may well reflect an N400-like effect, which is in general agreement with several previous studies showing N400-like enhanced negativity for semantically incongruous AV signals (e.g. Meyer, Harrison, & Wuerger, 2013;Proctor & Meyer, 2011;Zimmer et al, 2010) and affectively incongruous AV stimuli (Goerlich et al, 2012). While the N400 is generally associated with incongruences in linguistic stimuli (for a review, see Kutas & Federmeier, 2011), the N400 has also been shown to be evoked by nonlinguistic incongruency related to, for example, line drawing and sounds (Cummings, Moreover, the linguistic N400 component is usually reported as a centro-parieto deflection (Kutas & Federmeier, 2011), whereas the current data indicates a more frontal effect, in line with the topography from studies on the non-linguistic N400 (Cummings, Čeponienė, Koyama, Saygin, Townsend, & Dick, 2006;Ganis, Kutas, & Sereno, 1996).…”
Section: Discussionsupporting
confidence: 93%
“…emotional words) was evaluated faster when preceded by emotion-congruent primes (e.g. music) than when preceded by emotion-incongruent primes [41], [51], [53]. This emotional congruency effect was also embodied by a pronounced N400 effect in brain potentials 400–500 ms post target onset, and reduced superior temporal gyrus but increased fusiform gyrus activations, during emotion-incongruent than during congruent conditions [41], [42], [51].…”
Section: Introductionmentioning
confidence: 88%
“…In particular, based on previous work showing that the N400 (Kutas & Federmeier, 2011) and late positive component (LPC; Kutas & Federmeier, 2011;Friedman & Johnson, 2000) reliably represent the strength of cross-modal memory associations, we expected to find that AP musicians will manifest stronger N400 effects as well as increased LPC manifestations. The N400 component has previously repeatedly been shown to constitute an objective marker for investigating the conceptual relatedness between visual and auditory representations, such as, for example, graphemes and phonemes (Proverbio, Vecchi, & Zani, 2004) as well as written nouns and sounds (Goerlich et al, 2012). Furthermore, even so the exact functional processes reflected by the LPC are much less clear than those of the N400 (Friedman & Johnson, 2000), this component has been proposed to be driven by the allocation of memory resources (Chung, Tong, & McBride-Chang, 2012;Ohara, Lenz, & Zhou, 2006).…”
Section: Introductionmentioning
confidence: 99%